IMPROVING THE QUALITY OF MEMORIZATION OF AL-QUR’AN THROUGH THE IMPLEMENTATION OF TAKRIR METHOD IN ISLAMIC BOARDING SCHOOL MATHOLIB AS-SULUK CIREBON - Ilman Nafi'a; Septi Gumiandari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2022)
Many assume that people who have grown up do not have the opportunity to memorize the Qur'an because of the difficulties that will be faced in the process of memorizing it rather than in childhood. This research aims to find out (1) the application of the takrir method in Ponpes Matholib As-Suluk. (2) factors that affect students' ability to memorize by takrir method, (3) the quality of memorization of the holy verse of the Qur'an using the takrir method. This study uses descriptive qualitative methods. Through the technique of interviewing, observation and documentation studies, several findings were obtained: (1) the application of the takrir method in Ponpes Matholib As-Suluk was applied through the repetition of santri memorization in four ways: individual takrir, collective takrir with friends, takrir with teachers, and takrir at prayer time; (2) there are 2 factors that affect the application of takrir methods: internal (santri mood) and external factors (pesantren environmental support); and (3) the application of this method succeeded in improving the quality of santri memorization because the students were able to improve their memorization quite quickly and they were also able to reread verses and surahs that had been memorized quite smoothly.